137k views
4 votes
Solve for x: (x+a)(x-b) = x^2 -1

How do I solve this ?

User Sahas
by
5.1k points

2 Answers

1 vote

Explanation:

(x + a)(x - b) = x² - 1

(x + a)(x - b) = (x + 1)(x - 1)

By equality :

a = 1

b ÷ -1

User Ivan Davidov
by
5.3k points
1 vote

You must factor.


x^2-1=(x+1)(x-1)

The factored form is equal to the assigned form.


(x+1)(x-1)=(x+a)(x-b)

Values a, b correspond to the factored 1, -1.

Value of x however remains unknown. But we can change that.

Given factored result,


(x+1)(x-1)

We can set expression equal to 0 then find such x that when added with number a or b results with 0.


(x+1)(x-1)=0

Hence x has 2 solutions.


</p><p>x+1=0\Rightarrow\boxed{x_1=-1} \\</p><p>x-1=0\Rightarrow\boxed{x_2=1}</p><p>

Hope this helps.

User Changelog
by
5.1k points